Aplikasi Pemandu Transportasi Umum Kota Surakarta Berbasis Android - Yudi Artanto, Yustina Retno Wahyu Utami (STMIK Sinar Nusantara, 2013)
This research aims to develop a system that allows people to access information about transportation at Surakarta. This information includes bus stop locations, departure trains, taxis, and angkuta. The method used is observation, interviews, literature, and experiment. System design based on object-oriented paradigm that using UML. This application was built using Eclipse, Macromedia Dreamweaver, mysql databases, and digital maps taken from google maps. Based on questionnaires from 20 respondents, found that public transportation guide application android based at Surakarta has a attractive view, easy to use, very useful information. Keyword: android application, object oriented paradigm, transportation, uml.